Therapist and patient accountability through tactility and sensation in medical massage sessions - Satomi Kuroshima (Social Interaction, 2020)
This paper looks at the issue of therapists’ and participants’ accountability regarding a perceived problem in routine medical massage sessions. Specifically, it shows how therapists and patients communicate their tactile perception and sensation of the problem by negotiating their accountability for the current state of the treated body part. Drawing on video-recorded data of 12 routine medical massage sessions at home and five sessions at a clinic, this paper demonstrates that there is a normative order with regard to the participants’ accountability for the patients’ problems. In routine sessions, patients presumably have a problem (e.g., body stiffness or tension) that needs to be treated. The physical therapists’ accountability for the problem is usually displayed via direct access to the treated body part for their attentiveness to as well as validation of the patient’s claimed problem, making the medical treatment relevant. The patients are also accountable for their own problems as they are expected to have the primary right and obligation to look after their own health. Through multimodal and sensorial practices, therapists balance their medical and professional authority with their patients’ concerns, for which the patients claimed to have first-hand experience and independent access to the problem. The data is in Japanese.